Polarization-induced internal electric field to manipulate piezo-photocatalytic and ferro-photoelectrochemical performance in bismuth ferrite nanofibers. (March 2022) - You, Daotong; Liu, Lei; Yang, Zhiyong; Xing, Xiaoxuan; Li, Kaiwei; Mai, Wenjie; Guo, Tuan; Xiao, Gaozhi; Xu, Chunxiang
Abstract: Developing lead-free ferroelectrics BiFeO3 with polarized electric field for tuning charge-transport properties in piezo-photocatalytic and ferro-photoelectrochemical (PEC) is highly desired but also challenging, especially defects such as impurity phases and oxygen vacancies lead to the weak polarization and large leakage current of BiFeO3 . Here, we used a facile electrospinning strategy to modify BiFeO3 nanofibers by A-site Pr ion and B-site Mn ion co-doping. In this way, the concentrations of oxygen vacancies and valence of Fe 3+ to Fe 2+ were significantly inhibited, and the morphotropic phase boundary (MPB) of the rhombohedral (R) to tetragonal (T) phase was obtained, resulting in better ferroelectric performances and lower leakage current. Thus, BiPrFeMnO3 nanofibers was able to generate a large piezoelectric potential through magnetic stirring (piezoelectric effect) and light irradiation (photocatalytic effect), resulting in superior piezo-photocatalytic performance with a degradation rate of 0.1352 min −1 for rhodamine B, which was 8.29, 4.3 and 4.2 times higher than that of BiFeO3, BiPrFeO3 and BiFeMnO3, respectively. In addition, optimized PEC performance by controlling the polarization state was observed in BiPrFeMnO3 . The photocurrent could be effectively tuned by more than 16 times (8.2 −131.2 μA·cm −2 at 0 V vs Ag/AgCl) under irradiation of simulated sunlight by tuning the poling voltage between + 4 and − 4 V. Meanwhile, the onset potential switched from − 0.16 to − 0.18 V, which was favorable for the PEC reactions. Our present work gives a clear understanding of the role of ferroelectric polarization and solar energy conversion and provides a way to develop highly efficient piezo-/ferroelectric nanomaterials. Graphical Abstract: We propose elemental substitution of A-site and B-site in BiFeO3 -based Pb-free ferroelectric nanofiber to improve the ferroelectric properties and reduce the concentrations of oxygen vacancies and Fe 2+ . Furthermore, this driving force for charge separation directly contributes to the enhancement of the piezo-photocatalysis degradation of RhB and ferro-photoelectrochemical activity in Pr and Mn co-doped BiFeO3 ferroelectrics. ga1 Highlights: An effective strategy to improve the ferroelectric properties and reduce the concentrations of oxygen vacancies by introducing elemental substitution in BiFeO3 nanofibers. The BiPrFeMnO3 nanofibers possess superb piezo-photocatalysis degradation activity with a reaction rate of 0.1352 min -1, which is 8.3 times higher than BiFeO3 nanofibers. The photocurrent could be effectively tuned by 16 times (8.2−131.2 μA·cm −2 at 0 V vs Ag/AgCl) under light irradiation by tuning the poling voltage between +4 and −4 V.